2018
DOI: 10.1002/mc.22810
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid induces osteosarcoma cell apoptosis by inhibition of Notch signaling

Abstract: Oleanolic acid (OA), a naturally occurring triterpenoid, exhibits potential antitumor activity in several tumor cell lines. Although the inhibition effects of OA on proliferation and survival in human cancers have been confirmed, the potential mechanism underlying OA-induced osteosarcoma cell death has not yet been fully elucidated. Our results in this study showed that OA inhibits proliferation and viability of osteosarcoma cells in a dose-dependent manner. Flow cytometry assays revealed that apoptosis in ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…OA-induced cell death was ROS independent. OA has been reported to induce apoptosis in human hepatocellular carcinoma cells [21,22] , non-small cell lung cancer cell lines [23] , hypertrophic scar fibroblasts [24] and osteosarcoma cells [25] . In this investigation it was found that OA could decrease LO2 cell viability in a concentration-dependent manner.…”
mentioning
confidence: 99%
“…OA-induced cell death was ROS independent. OA has been reported to induce apoptosis in human hepatocellular carcinoma cells [21,22] , non-small cell lung cancer cell lines [23] , hypertrophic scar fibroblasts [24] and osteosarcoma cells [25] . In this investigation it was found that OA could decrease LO2 cell viability in a concentration-dependent manner.…”
mentioning
confidence: 99%
“…OA serves an antioncogenic role during malignant tumor development by inhibiting cancer cell proliferation, migration and invasion, and triggering cell death via apoptosis, autophagy or mitophagy (6,17,21). Multiple signaling pathways are associated with OA-mediated anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…OA enhances osteosarcoma cell apoptosis. Previous studies have reported that OA increased cell apoptosis in other tumors (6,13); therefore, the effects of OA on osteosarcoma cell apoptosis were assessed. The TUNEL staining results suggested that OA significantly increased osteosarcoma cell apoptosis compared with the Ctrl group (Fig.…”
Section: Oa Inhibits Osteosarcoma Cell Proliferation and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent study, (+)-oleanolic acid (6) was found to induce MG63 and Saos-2 human osteosarcoma cell apoptosis by targeting mitochondria in a Notch signaling-dependent manner [35]. By acting via a diverse range of cellular mechanisms, this endorses the potential of (+)-oleanolic acid for further development as an antitumor agent.…”
Section: Lupane-type Triterpenoidsmentioning
confidence: 93%